2005
DOI: 10.1111/j.1540-8159.2005.00095.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Dual‐Chamber Pacing Mode to Minimize Ventricular Pacing

Abstract: Despite the low long-term incidence of high-degree atrioventricular (AV) block and the known negative effects of ventricular pacing, programming of the AAI mode in patients with sinus node dysfunction (SND) remains exceptional. A new pacing mode was, therefore, designed to combine the advantages of AAI with the safety of DDD pacing. AAIsafeR behaves like the AAI mode in absence of AV block. First- and second-degree AV blocks are tolerated up to a predetermined, programmable limit, and conversion to DDD takes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…One of the most attractive options is to avoid unnecessary right ventricular pacing by adequate programming or by using algorithms specifically designed to minimise ventricular pacing in patients who do not require permanent right ventricular pacing 10 11. This option must be evaluated in each patient to avoid unnecessary right ventricular pacing with the risk of development of heart failure.…”
Section: Alternatives To Right Ventricular Apical Pacingmentioning
confidence: 99%
“…One of the most attractive options is to avoid unnecessary right ventricular pacing by adequate programming or by using algorithms specifically designed to minimise ventricular pacing in patients who do not require permanent right ventricular pacing 10 11. This option must be evaluated in each patient to avoid unnecessary right ventricular pacing with the risk of development of heart failure.…”
Section: Alternatives To Right Ventricular Apical Pacingmentioning
confidence: 99%
“…The SafeR algorithm (Sorin CRM, Clamart, France) was developed to provide a pacing mode that combines the benefits of AAI with the safety of DDD pacing . The recent randomized SaveR study confirmed the superiority of SafeR in reducing RV pacing when compared to standard DDD pacing in selected patients without high‐degree AV block and in a more general pacemaker population.…”
Section: Introductionmentioning
confidence: 99%
“…25 Wenckebach-like and 2:1 pacemaker behavior. A pacemaker is programmed with an atrioventricular interval (AVI) of 125 ms, a post-ventricular atrial refractory period (PVARP) of 225 ms and a maximum tracking rate (MTR) of 400 ms (Wenckebach interval = MTR − AVI + PVARP = 400 − 125 + 225 = 50 ms).…”
mentioning
confidence: 99%